The effect of PhageGuard intervention on Escherichia coli O157:H7 applied to beef hides - Martinez G., Andres I. (Zamorano: Escuela Agrícola Panamericana, 2024)
An in-plant study was conducted to assess the antimicrobial effectiveness of the Phage Guard intervention against E. coli O157:H7 in cattle stalls before slaughter. The reduction in microbial surface area was evaluated by collecting 500-600 cm2 hide samples from the cleanest area of the cattle during slaughter at the Gordon W. Davis Meat Laboratory. Three replicates, each comprising nine beef hide samples, were obtained. These samples were inoculated with an E. coli O157:H7 cocktail via spray application. Throughout the study, periodic collections of inoculated hide samples were performed, and bacterial loads were quantified using the Drop Dilution method and TEMPO System. The TEMPO System proved to be the most suitable and accurate method for quantifying E. coli O157:H7 on beef cattle hides. The study's findings revealed no significant differences between treatments. Potential factors contributing to this outcome included the chosen temperature and exposure time for the bacteriophage's optimal hatching, growth, multiplication, and lysis, typically 37 °C and 30 minutes. However, under the specified conditions, a substantial reduction in E. coli O157:H7 with the PhageGuard E product was not observed. In conclusion, the environmental temperature and exposure time (15 minutes), considering the minimum wait time for beef cattle before slaughter, were insufficient to produce significant reductions in bacteria.